Evaluation of the development unevenness of the Russian Federation regions by socio-economic resource components - V. E. Goncharenko; V. F. Korobova (Статистика и экономика)
In the state strategy of the economic security of the Russian Federation the increased differentiation of regions and municipalities on the level and pace of socio-economic develop-ment is indicated as the main challenges, as well as the insufficient funding of industrial production, a weak innovation activity, lagging behind in the development and implementation of new and emerging technologies, increasing differentiation of the population by the income level, lack of labour resources, reduced quality and accessibility of education, health care and, as a result, the decline in the quality of the human capital.The purpose of this paper is to develop a system of integral indicators of resource components of socio-economic potential of the regions of the Russian Federation based on a legitimate, credible and accessible statistical data for the evaluation of their development unevenness. Materials and methods. Resource potential of the region is being considered as a collection of six groups of socio-economic indicators: fixed funds, financial and investment resource, labour resource, science and innovation resources, information resource and social resource. Each group includes indicators that are directly related to the possibilities of production of goods and services. In accordance with the methodological approaches of the resource capabilities evaluation of the region on the basis of integral indicators the principles of completeness, adequacy, accessibility, universality and formalization of the indicators are used. Evaluation of a group of indicators and all indicators of groups as a whole is made according to the values of integral indicators of reduction or exaggeration in comparison with the reference values of the resource components. Various indicators in the group have a different level of im-pact on the gross regional product that is taken into account in assessing their weight indicators. Time series values of the resource components in each group correlate with the time series values of the gross regional product, the coefficients values of pair correlation are used to recalculate them into weighting coefficients. Formulas for evaluating the individual indicators in the group are developed, integral indicators of the group of resource components and integral indicators of the resource potential of the region as a whole.Results. Given the significant differentiation of regions of Russia according to various objective factors, it is considered appropriate to compare regions within Federal Districts. For the Central Federal District, the Moscow region is taken as the benchmark for comparison, and relative levels of reduction in the resource components of other regions are calculated relative to the level of indicators of its resource potential. Analysis of the data shows that the highest level of resource reduction components of the Ivanovo region is observed in the resource group of science and innovation – 77.1 %, resources of the fixed funds, financial-investment and labour resources are equal the value of this indicator – from 42.3% to 45.4 %. The integrated indicator of relative resource reduction components in the Ivanovo area totaled 41.9 %.Conclusion. Using statistical data for the Ivanovo and Yaroslavl regions as examples, calculations of integral indicators are carried out, which demonstrate the possibility of assessing the regional development unevenness by their resource component of socio-economic development.